2016
DOI: 10.3390/su8010061
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cropping Effects on Agricultural Sustainability in Alar Oasis of Xinjiang, China

Abstract: Abstract:Agricultural sustainability has become a major concern in arid regions of China. In order to better understand the influence of continuous cropping on soil quality, six experimental fields were established in the Alar Oasis of Xinjiang, including uncultivated land (as a zero year treatment duration) and five different continuous cropping years on cotton fields, with different cropping durations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Even though monocultural cropping can bring higher economic benefits for local farmers, it has been reported that long‐term monocultural cropping practice decreases soil quality and soil microbial diversity that jeopardizes the sustainability of long‐term land use. Long‐term management practices in the crop land such as excessive irrigation, fertilization, and monoculture farming patterns bring secondary problems, such as nutrients loss, destroying soil structure, and inducing secondary salinization (Gong, He, & Liu, 2016; Wei & Yu, 2018). Hence, rotation or intercropping systems that support higher plant diversity should be considered for the sustainability of the desert‐oasis ecotone.…”
Section: Discussionmentioning
confidence: 99%
“…Even though monocultural cropping can bring higher economic benefits for local farmers, it has been reported that long‐term monocultural cropping practice decreases soil quality and soil microbial diversity that jeopardizes the sustainability of long‐term land use. Long‐term management practices in the crop land such as excessive irrigation, fertilization, and monoculture farming patterns bring secondary problems, such as nutrients loss, destroying soil structure, and inducing secondary salinization (Gong, He, & Liu, 2016; Wei & Yu, 2018). Hence, rotation or intercropping systems that support higher plant diversity should be considered for the sustainability of the desert‐oasis ecotone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to altering soil nutrient status, the effect of continuous cropping may influence soil enzyme activities [10]. Soil enzyme activity is directly or indirectly affected by agricultural practices such as tillage and fertilization, including continuous cropping [17,18]. Soil enzymes are important components of soil as they are related to changes in nutrient status.…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected in the northern region of the Taklimakan Desert in Xinjiang, China (80°10’-84°36’E, 0°25’-41°10’N). The mean annual temperature of the area is approximately 10.4 °C, and the mean annual precipitation and evapotranspiration are roughly 50.4 mm, and 1800 mm, respectively (Gong L et al . 2016)The dominant plant species in this desert community are Populus euphratica, Halostachys caspica, Tamarix chinensis, Phragmites communis, Lycium ruthenicum, and Glycyrrhiza uralensis .…”
Section: Methodsmentioning
confidence: 99%
“…2015). Plant communities in the upper reaches of the Tarim Desert are an especially fragile ecological zone (Gong Lu et al . 2016), but have been understudied.…”
Section: Introductionmentioning
confidence: 99%